(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the hemodynamic changes during the reperfusion phases in patients with liver transplants from brain-dead donors at Viet Duc University Hospital from 2024 to 2025. Subjects and methods: A cross-sectional, retrospective study on patients with liver transplants from brain-dead donors from January 2024 to June 2025. The study indicators include: age, gender, indication for liver transplant, MELD score preoperative, inferior vena cava clamping technique, blood loss, blood transfusion, warm ischemia time, cold ischemia time, operative time; pulse, systolic blood pressure, diastolic blood pressure, mean blood pressure at the time points: before and after inferior vena cava clamping, before and after reperfusion clamp release. Results: 40 patients were included in the analysis. Blood pressure reduction of more than 30% during reperfusion occurred in 55% of patients. Bradycardia occurred in 42.5% and asystole occurred in 12.5% of patients. Patients with Child-Pugh C cirrhosis had a rate of hemodynamic disturbances during reperfusion of 100%, significantly higher than the groups of patients with Child-Pugh A and B. In the group of patients using classical techniques, the rate of hemodynamic disturbances during reperfusion was 90.5%, significantly higher than the group using piggyback technique. There were significant differences in MELD score, operative time and warm ischemia time between the two groups. There were no significant differences in age, cold ischemia time, blood loss and blood product transfusion during surgery between the two groups.